2021
DOI: 10.1007/s11239-021-02575-4
|View full text |Cite
|
Sign up to set email alerts
|

Global haemostatic tests demonstrate the absence of parameters of hypercoagulability in non-hypoxic mild COVID-19 patients: a prospective matched study

Abstract: Severe COVID-19 patients demonstrate hypercoagulability, necessitating thromboprophylaxis. However, less is known about the haemostatic profile in mild COVID-19 patients. We performed an age and gender-matched prospective study of 10 severe and 10 mild COVID-19 patients. Comprehensive coagulation profiling together with Thromboelastography and Clot Waveform Analysis were performed. FBC, PT, APTT, D-dimer, fibrinogen and CWA were repeated every 3 days for both groups and repeat TEG was performed for severe pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…The final full-text review included 163 reports, from which 123 studies did not meet the inclusion criteria and were excluded. A total of 40 studies comprising of 3764 patients met the including criteria and were included in this systematic review and meta-analysis [24] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] . Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The final full-text review included 163 reports, from which 123 studies did not meet the inclusion criteria and were excluded. A total of 40 studies comprising of 3764 patients met the including criteria and were included in this systematic review and meta-analysis [24] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] . Fig.…”
Section: Resultsmentioning
confidence: 99%
“…White et al [ 63 ] also looked at free PS antigen and compared it between 34 noncritical and 75 critical COVID-19 patients and observed similar extent of reduction (mean 52.1 vs 54.5 IU/dL; reference range 65–135). Fan et al [ 64 ] also looked at PS activity between 10 mild and 10 severe patients and found mild reduction, but no difference between mild and severe patients (median 74% vs 71%; reference range 55–130%).…”
Section: Ps and The Anticoagulant Systemmentioning
confidence: 99%
“…The majority of studies that have reported PS deficiency in COVID-19 patients have either reported free PS or PS activity, a clot time-based measurement of the APC cofactor activity of free PS [ 49 , 50 , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] ]. It is possible for total PS antigen to remain normal but free PS, and PS anticoagulant activity, to decrease.…”
Section: Free Ps Deficiencymentioning
confidence: 99%
“…We thank Muzaffar et al [ 1 ] for providing feedback on our study [ 2 ]. The aim of our study was to evaluate the haemostatic profile of mildly ill and severely ill COVID-19 patients.…”
Section: To the Editormentioning
confidence: 99%